MOLECULAR MARKERS ASSISTED GENETIC CHARACTERIZATION OF DIFFERENT SALT TOLERANT PLANT SPECIES - T. Mahmood; R. Aslam; S. Rehman; S. M. S. Naqvi (Journal of Animal and Plant Sciences, 2013)
Genetic diversity of thirteen salt tolerant plant species namely Pergularia tomentosa, Salvadora oleoides, Malcolmia africana, Peganum hermala, Capparis spinosa, Tamarix aphylla, Prosopis juliflora, Rhazya stricta, Cynodon dactylon, Aerva persica, Cymbopogon jwarancusa, Calotropis procera and Salavadora persica was determined by using RAPD markers. In total ten primers from the OPC series were used, out of which nine primers gave reproducible amplification profiles. Out of the nine all except OPC-1, produced polymorphic bands and Numerical Taxonomy and Multivariate Analysis System (NTSYS) revealed 56% similarity among the selected species. Monomorphic bands produced by OPC-1 may be related to some genetic elements involved in managing the life under high salt conditions. There is a need to further find out the relationship of these monomorphic bands with genes involved in salt tolerance. Such type of genetic resemblance among halophytes should be further studied for the utilization of rich gene pool for crop improvement.
Keywords: Genetic Diversity; RAPD; Salt tolerance